1999
DOI: 10.1177/026988119901300412
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week study comparing moclobemide and sertraline in the treatment of outpatients with atypical depression

Abstract: One hundred and ninety-seven outpatients with atypical depression [Atypical Depression Diagnostic Scale (ADDS) score=4] were randomized to 12 weeks of double-blind treatment with sertraline or moclobemide in a multicentre, parallel-group clinical trial. Patients were started on either 50 mg/day sertraline or 300 mg/day moclobemide. If the therapeutic response was not satisfactory after 4 weeks, the dose could be increased to either 100 mg/day sertraline or 450 mg/day moclobemide. Primary efficacy evaluations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 17 publications
1
18
0
4
Order By: Relevance
“…The CGIbased response rate in our study is comparable to the CGI-based response rates seen in randomized controlled clinical trials with fluoxetine (51%), imipramine (53%), phenelzine (61%-85%), sertraline (77.5%), and moclobemide (67.5%) in MDD with atypical features. 3,[15][16][17][18] Interestingly, the magnitude of improvement in primary outcome measure and responder rate was consistent with the results from registration clinical trials of escitalopram for MDD. [36][37][38] In addition, our responders continued to maintain their response until the end of study, without fluctuation of the response.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The CGIbased response rate in our study is comparable to the CGI-based response rates seen in randomized controlled clinical trials with fluoxetine (51%), imipramine (53%), phenelzine (61%-85%), sertraline (77.5%), and moclobemide (67.5%) in MDD with atypical features. 3,[15][16][17][18] Interestingly, the magnitude of improvement in primary outcome measure and responder rate was consistent with the results from registration clinical trials of escitalopram for MDD. [36][37][38] In addition, our responders continued to maintain their response until the end of study, without fluctuation of the response.…”
Section: Discussionsupporting
confidence: 78%
“…16 These 2 studies support the use of SSRIs for atypical depression, but conclusions are limited by small sample sizes and lack of placebo arms. A randomized, parallel group, 12-week study comparing moclobemide and sertraline in the treatment of outpatients with MDD with atypical features (N = 197) also demonstrated that both medications produced comparable improvement 17 ; this larger study provides useful data, although it too is limited by the lack of a placebo arm and has been criticized 14 due to the suboptimal dose used in the moclobemide arm (mean dose of 410.2 mg/day). A 10-week, randomized, placebo-controlled study of MDD with atypical features (N = 154) showed that fluoxetine was superior to placebo, was comparable to imipramine in terms of efficacy, and was better tolerated than imipramine.…”
mentioning
confidence: 91%
“…As moclobemide, a selective and reversible inhibitor of MAO A (RIMA), appears to be less effective than older MAOIs such as phenelzine and DSM-IV criteria for atypical depression ME Thase tranylcypromine (Lotufo-Neto et al, 1999), the metaanalysis may have overestimated the relative effectiveness of the SSRIs. Consistent with this, strong trends favored sertraline over moclobemide in the larger of the two studies of the RIMA (Sogaard et al, 1999). Nevertheless, it is true that in the only study to contrast an SSRI, fluoxetine (n ¼ 20), with phenelzine (n ¼ 20), both treatments were highly effective and tolerability indices favored the newer medication (Pande et al, 1996).…”
Section: Validity Of Dsm-iv Atypical Depressionmentioning
confidence: 70%
“…Ancak son 10 yıl içerisinde yapılmış olan çalışmalar atipik depresyon tanı ölçütlerinin geçerliliğini yeniden tartışmaya açmıştır. [41][42][43][44][45][46][47][48][49] DSM-IV sonrası yapılan çalışmalar depresyonda atipik özelliğin major depresyona ve distimiye dahil edilmesini destek-lemiştir, ancak bu çalışmalar atipik depresyonlu hastaların hastalık seyri, biyoloji, tedavi yanıt beklentisi ve ailesel yüklülük açısından farklı olduğunu dü-şündürmüştür. [44] Bugün için en tartışmalı olduğu iddia edilen tanı ölçütü duygudurumda tepkisellik olmuştur.…”
Section: Atipik Depresyonun Tanı öLçütleriunclassified
“…Sogaard ve arkadaşları sertralin'in atipik depresyon tedavisinde moklobemid'den anlamlı olarak daha etkin olduğunu bildirmişlerdir. [41] Pande ve arkadaşları 42 atipik depresyon olgusunda fluoksetin'i, fenelzin kadar etkili olduğunu bulmuşlardır. Fluoksetin daha az yan etki göstermiş ve daha iyi tolere edilmiştir.…”
Section: Seçici Serotonin Gerialım İnhibitörleri (Ssri)unclassified